Current Controversies in Sepsis Management - Moss, Stephanie R.; Prescott, Hallie C. (Seminars in Respiratory and Critical Care Medicine, 2019)
The overarching goals of early sepsis management include early recognition, appropriate antibiotic therapy and source control, maintenance of hemodynamic stability, and supportive care of organ dysfunction. Despite increasing awareness of the global burden of sepsis, and general agreement on the goals of management, there is ongoing controversy regarding the implementation of specific treatment strategies to optimize patient outcomes. This article will address five current points of controversy in the management of sepsis and septic shock. These include optimal timing of antibiotics in patients with potential sepsis, the role of glucocorticoids in septic shock, vitamin C as a novel therapy for sepsis, the ideal intravenous fluid for resuscitation, and the optimal balance of fluid resuscitation and vasopressor administration in septic shock. For each of these topics, we review relevant literature, discuss areas of controversy, and present our current approach to management.
Keywords: septic shock; sepsis; hydrocortisone; critical illness; resuscitation